An Actor-Network Theory conceptualization for smart specialization strategies (S3): creative brokerage towards sustainability transition - Christopher Meyer (Entrepreneurship and Sustainability Issues)
Smart Specialisation Strategies, their planning and implementation are becoming more important in Europe's transition but also bring up several challenges, especially when it comes to complex innovation processes and requirements arising from the call for sustainable development on several levels. Even though the concept of Smart Specialisation has been elaborated on in a lot of research, the literature still lacks sufficient theoretical justification for the policy concept, resulting in a gap between theory and practice in terms of Smart Specialisation Strategy design and implementation. In this context, this paper provides cross-linkages to evidentially drivers of sustainability transition such as social innovation, cross-border cooperation, Entrepreneurial Discovery Processes and creative innovation. The exploration of synergies towards these concepts under S3 is still scant. The conducted research is based on an extensive literature review and uses a comparative analysis of Smart Specialisation and Actor-Network Theory. By applying Actor-Network Theory within Smart Specialisation Strategy research discourse, known problems of the concept might be overcome, Entrepreneurial Discovery Processes can be improved, and critical concepts for sustainability transition can be well incorporated into S3 understanding. In this, conducted research is also breaking new ground in theoretical conceptualization by providing the analysis and crosslinks of Actor-Network Theory with Smart Specialisation Strategies. Moreover, the integration of essential aspects towards sustainability transition under S3 can be enabled through the Actor-Network Theory application as it opens further research streams to be integrated into Smart Specialisation, such as social innovation and creative industries.